Possible cause underlying gastric necrosis and perforation: Celiac artery thrombosis - Peker, Ahmet; Yarkıcı, Hakan; Ertürk, Elif; Akar, Harun (Journal of Surgery and Medicine, 2017)
In this article, we are sharing a case of a 76-year-old woman with known hypertension, atrial fibrillation,diabetes mellitus, coronary artery disease, who is presenting with stomach necrosis and perforation possibly due to celiac artery thrombosis after newly developed abdominal pain and bloody vomiting. In our case, emergency surgery was planned and the patient refused the operation and was lost at 48 hours of clinical follow-up. We aimed to discuss the etiology of celiac artery thrombosis, briefly. We believe that necrosis and perforation of the stomach due to celiac artery thrombosis deserves to be shared because it is a rare and difficult case to manage.